RNA Binding Protein Regulation and Cross-Talk in the Control of AU-rich mRNA Fate - García-Mauriño, Sofía M.; Rivero-Rodríguez, Francisco; Velázquez-Cruz, Alejandro; Hernández-Vellisca, Marian; Díaz-Quintana, Antonio; De la Rosa, Miguel A.; Díaz-Moreno, Irene (Frontiers in Molecular Biosciences, 2017)
mRNA metabolism is tightly orchestrated by highly-regulated RNA Binding Proteins (RBPs) that determine mRNA fate, thereby influencing multiple cellular functions across biological contexts. Here, we review the interplay between six well-known RBPs (TTP, AUF-1, KSRP, HuR, TIA-1 and TIAR) that recognize AU-rich elements (AREs) at the 3' untranslated regions of mRNAs, namely ARE-RBPs. Examples of the links between their cross-regulations and modulation of their targets are analyzed during mRNA processing, turnover, localization and translational control. Furthermore, ARE recognition can be self-regulated by several factors that lead to the prevalence of one RBP over another. Consequently, we examine the factors that modulate the dynamics of those protein-RNA transient interactions to better understand the final consequences of the regulation mediated by ARE-RBPs. For instance, factors controlling the RBP isoforms, their conformational state or their post-translational modifications can strongly determine the fate of the protein-RNA complexes. Moreover, mRNA specific sequence and secondary structure or the subtle environmental changes are also key determinants to take into account. To sum up, the whole understanding of such a fine tuned regulation is a challenge for future research and requires the integration of all the available structural and functional data by in vivo, in vitro and in silico approaches.